THE ROLE OF PAROXETINE IN POSTMENOPAUSAL HOT-FLASHES FREQUENCY REDUCTION - Zareen Naz; Moosa Khan; Faiz Ahmed Siddiqui; Faiza Siddiqui (ziauddin University, 2019)
Background: To evaluate the effects and safety profile of Paroxetine on hot - flashes in post - menopausal women. Methods: It was prospective open label control clinical trial. This study is conducted in the Department of pharmacology & Therapeutics in collaboration with the Department of Obstetrics & Gynecology JPMC. The patients were selected from outpatients department (OPD) of Obstetrics & Gynecology. Duration of the study was 12 month from January 2014 to January 2015. Enrolling 180 outpatients who had menopause with hot flushes divided into three groups. The Greene Climacteric Score Scaling was applied to observe the effects of 12.5mg, 20mg Paroxetine on frequency of hot flashes as compared to Placebo. Results: Mean GCS scoring frequency in 12.5mg Paroxetine group at 12 week was 1.97±0.31 and the baseline 2.64±0.29. In 20mg Paroxetine mean GCS at baseline was 2.76±0.23 and 12 week 2.04±0.12. Where as in Placebo mean GCS scoring frequency at 12 week was 2.80±0.24 and at baseline 2.76±0.24. Conclusion: The frequency of hot flashes with Paroxetine 20mg and 12.5mg, is significantly reduced in post menopauseal women as compared to Placebo.